2004
DOI: 10.4314/eamj.v80i10.8752
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV/AIDS and psychiatric disorders and their related risk factors among adults in Epworth, Zimbabwe

Abstract: Objectives: To examine the prevalence of HIV infection, neuropsychiatric disorders, psychiatric symptoms/signs, alcohol use/misuse, CD4 cell counts and risk factors in adult patients. Design: Cross-sectional study. Setting: Epworth, which is about 15km on the southeastern part of Harare, Zimbabwe. Subjects: Two hundred subjects were included in the study out of which six were excluded beacause of HIV-1 indeterminate results. Materials and Methods: A convenience sample of 200 subjects recruited in a crosssectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
3
23
4
1
Order By: Relevance
“…An unmatched case control study among men and women visiting HIV testing and counselling centres found that persons who had used alcohol at some stage in their life were significantly more likely to be HIV+ than those who had never used alcohol (Seme et al, 2005) Two of the community/population-based studies involving both men and women that used an ever use/never use dichotomy (last month or lifetime use) found that persons who had used alcohol were significantly more likely to be HIV+ than persons who had not used alcohol over the specified time period (Hargreaves et al, 2002;Mbulaiteye et al, 2000). These findings conflict with those of another study that found no significant difference between current users and non-users of alcohol with regards to HIV prevalence (Sebit et al, 2003). The last study in this group found that the consumption of local brew or bottled alcohol at least once per week was significantly associated with HIV-1 infection among men, but not among women (Mmbaga et al, 2007).…”
Section: Original Articlecontrasting
confidence: 56%
See 1 more Smart Citation
“…An unmatched case control study among men and women visiting HIV testing and counselling centres found that persons who had used alcohol at some stage in their life were significantly more likely to be HIV+ than those who had never used alcohol (Seme et al, 2005) Two of the community/population-based studies involving both men and women that used an ever use/never use dichotomy (last month or lifetime use) found that persons who had used alcohol were significantly more likely to be HIV+ than persons who had not used alcohol over the specified time period (Hargreaves et al, 2002;Mbulaiteye et al, 2000). These findings conflict with those of another study that found no significant difference between current users and non-users of alcohol with regards to HIV prevalence (Sebit et al, 2003). The last study in this group found that the consumption of local brew or bottled alcohol at least once per week was significantly associated with HIV-1 infection among men, but not among women (Mmbaga et al, 2007).…”
Section: Original Articlecontrasting
confidence: 56%
“…A cross-sectional study was conducted in Epworth, Zimbabwe, to determine the overall prevalence of HIV and psychiatric disorders and their related risk factors among 194 adults in this less affluent community (Sebit et al, 2003). Two sample populations and two sampling methods for subject recruitment were used.…”
Section: Community/population-based Studiesmentioning
confidence: 99%
“…Across Africa, however, reports of alcohol use among HIV positive persons show variable rates. Sebit et al observed a prevalence of alcohol use/misuse among HIV positive adult outpatients in Zimbabwe of 24.3% (Sebit et al 2003), while Shaffer et al recorded 54% of both HIV positive and negative public clinic patients in Kenya as hazardous drinkers according to the AUDIT (Shaffer et al 2004). Past alcohol use was more common than current use suggesting that participants may have decreased their level of alcohol consumption concurrent with entering medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 20 studies included in Fisher and colleagues' meta-analysis, 19 were retained for inclusion in the present study (Ao, Sam, Masenga, Seage, & Kapiga, 2006;Ayisi et al, 2000;Braddick et al, 1990;Demissie, Amre, & Tsega, 1996;Fritz et al, 2002;Hargreaves et al, 2002;Kapiga, Lyamuya, Lwihula, & Hunter, 1998;Kapiga et al, 2002;Kapiga et al, 2006;Lewis et al, 2005;Mbulaiteye et al, 2000;Mnyika, Klepp, KvĂ„le, & Ole-King'ori, 1996;Ndina-Achola et al, 1997;Sebit et al, 2003;Simbayi et al, 2004;Talbot et al, 2002;Tengia-Kessey, Msamanga, & Moshino, 1998;Zablotska et al, 2006;Zuma, Gouws, Williams, & Lurie, 2003) and one (Gilgen, Williams, & Campbell, 2000) was excluded for failing to meet the inclusion criteria specified below (i.e., it was not published in a peer-reviewed journal). An additional eight nonoverlapping studies published prior to 2009 were identified from our previous narrative review (Allen et al, 1992;Bassett et al, 1996;Clift et al, 2003;Dunkle et al, 2004;Fisher, Cook, Sam, & Kapiga, 2008;Msuya et al, 2006;St.…”
Section: Methods Literature Reviewmentioning
confidence: 99%